BS IEC 61008-2-2. Residual current operated circuit-breakers without integral overcurrent protection for household and similar uses (RCCB's). Part 2-2. RCCBs according to 4.1.2, 4.1.3, 4.1.4, 4.1.5 and 4.1.6 (4th December 2020) - British Standards Institution,
No abstract available